Compensation, Career Development, and Job Satisfaction as the Antecedent of Nurse Turnover Intention - Nur Hidayah; Hana Rizki Ananda (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
The shortage of professional nurses in a hospital is to threaten service quality and patient safety. Inadequate compensation, no career development, and dissatisfaction can increase turnover intention. Increasing professional nurses' resilience is better than recruiting new nurses from an economic perspective. The research analyzed the effect of compensation and carrier development on job satisfaction and the impact on nurses' turnover intention in a private hospital in Yogyakarta, Indonesia. A quantitative research design with the cross-sectional approach was used. The sampling technique was simple random sampling. The samples consisted of 47 nurses who made a self-reported by filling out the questionnaire. Data analysis used Partial Least Square. The study found that compensation and career development had direct and significant effects on Turnover Intention. Moreover, compensation and career development also had indirect and significant Turnover Intention effects through job satisfaction as the intervening variable.